2021
DOI: 10.1111/pace.14140
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical targets and expected outcomes of catheter‐based ablation of atrial fibrillation in 2020

Abstract: Anatomical‐based approaches, targeting either pulmonary vein isolation (PVI) or additional extra PV regions, represent the most commonly used ablation treatments in symptomatic patients with atrial fibrillation (AF) recurrences despite antiarrhythmic drug therapy. PVI remains the main anatomical target during catheter‐based AF ablation, with the aid of new technological advances as contact force monitoring to increase safety and effective radiofrequency (RF) lesions. Nowadays, cryoballoon ablation has also ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 132 publications
(182 reference statements)
0
9
0
Order By: Relevance
“… 40 Since then, the role of PVs on AF initiation has mobilized a tremendous amount of predominantly private funding to achieve rapid, effective, and safe PVI using different technologies like single-shot devices, 41 contact force monitoring, or high-resolution electroanatomical mapping, 42 , 43 among others. 5 Conversely, experimental data for the necessary understanding of the mechanisms underlying AF maintenance beyond the PVs have been much more limited and mainly associated with public funding agencies. 44 , 45 …”
Section: Historical Perspective: Experimental Bases For Current Mechanistic Approaches In the Clinicmentioning
confidence: 99%
See 3 more Smart Citations
“… 40 Since then, the role of PVs on AF initiation has mobilized a tremendous amount of predominantly private funding to achieve rapid, effective, and safe PVI using different technologies like single-shot devices, 41 contact force monitoring, or high-resolution electroanatomical mapping, 42 , 43 among others. 5 Conversely, experimental data for the necessary understanding of the mechanisms underlying AF maintenance beyond the PVs have been much more limited and mainly associated with public funding agencies. 44 , 45 …”
Section: Historical Perspective: Experimental Bases For Current Mechanistic Approaches In the Clinicmentioning
confidence: 99%
“…A common strategy to treat symptomatic AF episodes after permanent PVI is to ablate other atrial anatomical targets, potentially associated with AF initiation and maintenance. 5 Among other regions, the posterior left atrial wall, the vein of Marshall, and the left atrial appendage (LAA) have been reported to be locations for AF triggers outside de PVs in some series. 5–7 Moreover, extra-PV trigger locations may also participate in AF maintenance as areas for driver sources sustaining the overall arrhythmia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the optimal ablation strategy beyond pulmonary vein isolation (PVI) for PersAF remains unclear. [ 3 ] A wide variety of adjunctive ablation strategies have been explored, such as linear ablation, posterior wall isolation, ganglionic plexus ablation, isolation of the left atrial appendage, or substrate modification of areas with low voltage and fibrosis among others. [ 4 9 ] While incremental benefit has been reported with some of these approaches, other studies have failed to show any advantage.…”
mentioning
confidence: 99%